Remote third shift EAST operation: a new paradigm. (31st March 2017) - Schissel, D.P.; Coviello, E.; Eidietis, N.; Flanagan, S.; Garcia, F.; Humphreys, D.; Kostuk, M.; Lanctot, M.; Lee, X.; Margo, M.; Miller, D.; Parker, C.; et al.
Abstract: General Atomics' (GA) scientists in the United States remotely conducted experimental operation of the experimental advanced superconducting tokamak (EAST) in China during its third shift. Scientists led these experiments in a dedicated remote control room that utilized a novel computer science hardware and software infrastructure to allow data movement, visualization, and communication on the time scale of EAST's pulse cycle. This Fusion Science Collaboration Zone infrastructure allows the movement of large amounts of data between continents in a short time scale with a 300-fold increase in data transfer rate over that available using the traditional transmission protocol. Real-time data from control systems is moved almost instantaneously. An event system tied to the EAST pulse cycle allows automatic initiation of data transfers, resulting in bulk EAST data to be transferred to GA within minutes. The EAST data at GA is served via MDSplus to approved US collaborators avoiding multiple US clients from requesting data from EAST and competing for the long-haul network's bandwidth. At present there are 37 approved scientists from 8 US research institutions.